Modele i typologie procesu rozwodowego - Rydzewski, Paweł (Wydział Prawa i Administracji UAM, 1991)
Relatively recently there appeared attempts to systemize divorce as a phenomenon of a processual character. So far, attention has been focused mostly on socio-demographic aspects of divorce, on its causes, consequences, etc. A newapproach to divorce is characterized by the shift of attention to divorce as a process and to its internal dynamics. Besides, efforts are directed at the systematization of the course of this process. Building models and typologies of the divorce process is the indication of attempts going in that direction. Models of the divorce process are built on the assumption that the course of divorce processes may be reduced to a relatively stable scheme in time. The author evaluates such models and synthesizes his findings. Typologies of the divorce process attempt at systematizing different patterns of marital dissolution and define some typical ways of getting divorce. The article contains the presentation and evaluation of the moost important typologies formulated by K. Kressler and J. Ponzetti. In this context it is important to differentiate between the dissolution process and the divorce process. The latter comprises not only the period preceding the divorce in a legal sense, but also the period of divorce adjustment.
Models and typologies of the divorce process